Bicycle use in Latin American cities: changes over time by socio-economic position - Avila-Palencia, Ione; Sarmiento, Olga L.; Gouveia, Nelson; Jáuregui, Alejandra; Mascolli, Maria A.; Slovic, Anne D.; Rodríguez, Daniel A. (Frontiers in Sustainable Cities, 2023)
Introduction We aimed to examine utilitarian bicycle use among adults from 18 large Latin American cities and its association with socio-economic position (education and income) between 2008 and 2018. Methods Data came from yearly cross-sectional surveys collected by the Development Bank of Latin America (CAF). A total of 77,765 survey respondents with complete data were used to estimate multilevel logistic regression models with city as random intercept and year as random slope. Results Individuals with high education and high-income levels had lower odds of using a bicycle compared with participants with lower education and income levels. These associations, however, changed over time with the odds of bicycle use increasing for all groups, especially among individuals with the highest education and income levels. Discussion Our results confirm the broadening appeal of bicycling across socio-economic positions in several Latin American cities and reinforce the importance of considering policies aimed at supporting and enhancing bicycle travel for all users.